2018
DOI: 10.1080/17482631.2018.1479583
|View full text |Cite
|
Sign up to set email alerts
|

A challenging entanglement: health care providers’ perspectives on caring for ill and injured tourists on Cozumel Island, Mexico

Abstract: Purpose: Despite established knowledge that tourists often fall ill or are injured abroad, little is known about their treatment. The intent of this study was to explore health care professionals’ treatment provision experiences on Cozumel Island, Mexico. Methods: 13 semi-structured interviews were undertaken with professionals across a number of health care vocations on Cozumel Island. Interviews were transcribed and thematically analysed to determine common challenges faced in the provision of treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…For example, research on medical tourism has shown that patients may not understand differences in the roles that health workers in destination hospitals take on relative to what they are familiar with in their home systems, which can create confusion [40,41]. Further to this, in the context of caring for ill and injured vacationers, interviews with health care providers in a popular vacation destination in Mexico point to how misunderstandings based on stereotypes regarding practice competency can affect patients' decisions regarding receiving treatment for injuries sustained on holiday while abroad [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research on medical tourism has shown that patients may not understand differences in the roles that health workers in destination hospitals take on relative to what they are familiar with in their home systems, which can create confusion [40,41]. Further to this, in the context of caring for ill and injured vacationers, interviews with health care providers in a popular vacation destination in Mexico point to how misunderstandings based on stereotypes regarding practice competency can affect patients' decisions regarding receiving treatment for injuries sustained on holiday while abroad [42].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring such questions has the potential to deepen the insights gleaned in the current study. Second, given the sizeable number of Canadians who participate in international retirement migration and the country's rapidly aging population [42], it is an opportune time to explore models and mechanisms for enhancing care continuity for those who participate in this transnational practice. Doing so has the potential to respond to some of the challenges identified by the focus group participants.…”
Section: Discussionmentioning
confidence: 99%